KEDUDUKAN BADAN PERADILAN KHUSUS PERSELISIHAN HASIL PILKADA BERDASARKAN UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA 1945 (JURNAL HUKUM SEHASEN, 2019)
The enactment of the elections is a mandate from the issuance of Law Number 1 Year 2015 on the Stipulation of Government Regulation in Lieu of Law No. 1 of 2014 on the Election of Governors, Mayors and Regents into thelaws, and the enactment of Law No. 8 of 2015 on Changes Upon Act 1 of 2015 Concerning Government Regulation in Lieu of Law No 1 of 2014 on the Election of Governors, Regents and Mayors into (THE) Laws. Then the government and the legislature revised the law on the election of regional headsagain with the issuance of Law Number 10 Year 2016 About the Second Amendment to Law Number 1 Year 2015 On Stipulation of Government Regulation in Lieu of Law Number 1 Year 2014 About Election Governors, Regents, and Mayors Become theLaws. Where in the legislation states that the legislature determines the special election court which then continues with the agreement between the government and the House of Representatives to establish a special court in no later than 2024. This research entitled The Status of the Special Court for Electoral Disputes Dispute Based on the Constitution of the State Republic of Indonesia Year 1945. This research is normative law research using approach of law (statute approach). The result of the research shows that the position of the special judicial institution for the settlement of election result of the regional head if it is outside the judicial authority is unconstitutional according to the 1945 Constitution. Therefore, the establishment of a special court for the settlement of election disputes must be under the Supreme Court. KEY WORDS : Position, Special Election Judiciary Body Election Results Dispute.